Stressful but Not Unhappy: A Review of the Positive Aspects of Parenting a Child with Autism Spectrum Disorder - Kenneth Curley; Robert Hughes; Yasuhiro Kotera (Children)
This review aimed to identify and synthesise the evidence for the positive aspects of parenting a child with autism spectrum disorder (ASD). To date, ASD parental research has predominantly focused on the negative aspects; parents and carers are left uninformed of how to strengthen their positive mental wellbeing. Three electronic databases—PubMed, Scopus, and Web of Science —were searched for literature reporting positive aspects of parenting a child with ASD, published between January 2013 and December 2023. The PRISMA 2020 checklist was used for reporting. Two hundred and fifty-four articles were retrieved from the databases. After title/abstract screening (n = 213) and full-text reviews (n = 32), six papers were included (n = 6). Sixteen positive aspects of parenting a child with ASD were identified and grouped into three themes: joyful moments, journey to resilience, and social connection. These three themes are eudaimonic wellbeing constructs and often under-represented in ASD parental studies. Focusing on joyful moments, building resilience through the parenting journey, and finding support and connection with others in similar situations can support the mental wellbeing of parents and carers of children with ASD. Future research is needed to further evaluate the positive aspects of parenting a child with ASD.